Increases in nitrogen use efficiency decrease nitrous oxide emissions but can penalize yield in sugarcane - Chalco Vera, Jorge (2022)
Fil: Chalco Vera, Jorge. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Salta (EEA Cerrillos). Cerrrillos, Salta, Argentina.